Un breve volo nella filosofia tedesca: che relazione c’è tra la vita e il pensiero? - Safranski Rüdiger; Homberg, Annelore; Spielmann, Thomas (Il sogno della farfalla, 2010)
In the interview Rüdiger Safranski explores the reasons that have led to the writing of his books, among which his famous monographs on Schopenhauer, Nietzsche and Heidegger and his treatises on such wide ranging themes such as truth, evil, globalization. Safranski claims to be particularly interested in the relationship that exists between philosophical thought and the life of the thinker. Among these dimensions there could be a conspicuous scission, as in the case of Schopenhauer, a final “short circuit” (Nietzsche), an odd attempt towards unification (Heidegger) or a spontaneous coherence as in the case of Schiller and Goethe.